LIBERALISATION AND EFFICIENCY OF INDIAN COMMERCIAL BANKS: A STOCHASTIC FRONTIER ANALYSIS - H P Mahesh (INSTITUTE FOR SOCIAL AND ECONOMIC CHANGE, 2006)
The reforms introduced after 1992 are expected to have an impact on the performance of commercial banks. Thus the present study attempts to examine the efficiency level of Indian banks for the period 1985-2004. We employ the technique of stochastic frontier analysis to estimate bank specific cost, profit and advance efficiencies. Our results show that deregulation has significant impact on all three types of efficiency measures. Public sector banks rank first in two of the three efficiency measures showing that, as opposed to the general perception, these banks do not lag behind their private counter parts.